Pengaruh Terapi Musik Terhadap Penurunan Kecemasan: Tinjauan Literatur - Naibaho, Amelia Elisabeth; Fadhila, Filza; Daulay, Wardiyah (STIKES Ngesti Waluyo, 2024)
Anxiety is a condition that can be caused by several factors, both internal and external. Anxiety can have negative impacts on individuals. Anxiety can be overcome with several therapies, one of which is music therapy. Music therapy plays a role in releasing individual feelings about emotional problems, creating positive moods, helping with problem-solving, and resolving personal conflicts. This research was conducted using the Literature Review method. A literature search was carried out regarding the Effect of Music Therapy on Reducing Anxiety in the following databases: Science Direct, Google Scholar, and PubMed. Searches related to titles are limited in time from 2019-2023. Basically, music can be preventive to heal sufferers who experience social, emotional, or mental intelligence, and as a non-pharmacological intervention for nurses in caring for patients so they are not too anxious.